Effect of Seedling Rates on Crop Yield and Methane Emissions from Rice Paddies - Qiping Chen; Hao Li; Hexian Huang; Wei Wang (Atmosphere)
Agricultural strategies are urgently needed to mitigate greenhouse gas emissions without reducing crop yield. Seedling rate per hill will affect the quantity and quality of tillers, which may affect rice yield and CH4 emissions. Therefore, it is hypothesized that high yields with low yield-scaled CH4 emissions could be achieved with optimal seedling rate per hill. A field experiment was conducted with three densities (low seedling rate, LSR; moderate seedling rate, MSR; and high seedling rate, HSR) for two consecutive rice seasons. The CH4 fluxes were determined by the static chamber–GC method. The results showed no significant differences in rice yields, seasonal CH4 emissions, or yield-scaled CH4 emissions between the three treatments. For early rice, the HSR tended to achieve high yield without increasing yield-scaled CH4 emissions. As for late rice, the MSR showed similar rice yield, and tended to have lower yield-scaled CH4 emissions in comparison with the HSR. The results suggest that choosing an appropriate seedling rate per hill to increase grain yield while maintaining lower or comparable yield-scaled CH4 emissions can be a promising option to reduce CH4 emissions from rice paddies.